A Cross-Sectional Study on Functional Disability among the Elderly in Rural Area of Goa - Arya Ravi; Vanita G. Pinto Da Silva (Indian Association of Preventive and Social Medicine, 2024)
Introduction: Functional disability among the elderly reduces autonomy, leading to dependency, decreased quality of life, increased hospitalization, and higher mortality rates, ultimately lowering general life expectancy and increasing disabled life expectancy. Objectives: 1. To estimate the prevalence of functional disability among the elderly residing in the field practice area of Rural Health and Training Centre, Mandur, Goa. 2. To determine the factors associated with functional disability among study participants Methods: A community-based cross-sectional study was conducted among elderly individuals (aged 60 years and above) in the field practice area of Rural Health and Training Centre, Mandur, Goa. Systematic random sampling recruited 372 participants from 1,588 households. Functional disability was assessed using the Barthel Index, with data analysed using SPSS 22.0. Prevalence was expressed as a percentage, and associations were evaluated using significance tests and Odds ratios with 95% confidence intervals. Results: Out of 372 participants (mean age: 71.24 ± 8.03 years), 95 (25.5%) had functional disabilities in ADL, visual, or hearing impairments. Significant associations were found with age, literacy, financial dependence, and current alcohol consumption (p < 0.05). Conclusion: The high prevalence of functional disability among the elderly in rural Goa highlights the need for targeted interventions to improve quality of life and independence. Health education, literacy, and financial support are critical for preserving functional abilities. Community based initiatives and supportive healthcare policies are essential for reducing disability and healthcare costs among the elderly